Contributions of humanistic vision of the concept of social responsibility, from elements of critical theory [Aportes de la visión humanista al concepto de responsabilidad social, a partir de elementos de la teoría crítica] (2015)
This paper aims to identify contributions from the humanist vision to the concept of Social Responsibility using elements of Critical Theory, in order to understand the gaps between discourse and praxis in a context of large companies. Additionally, the most relevant results of the fieldwork are presented, showing how it became evident that there is a praxeological gap related to Social Responsibility in the large companies analyzed. The methods of this study considered three stages: conceptualization around Social Responsibility and Critical Theory; empirical work based on a sample of 42 companies, and consideration of the concept of Social Responsibility from a humanistic vision using elements of Critical Theory.